Exergy Analyses of Vehicles Air Conditioning Systems for Different Refrigerants - KEVEN, Arzu (International Journal of Computational and Experimental Science and Engineering, 2023)
There are a limited number of studies in the literature that include detailed exergy analysis of vehicle air conditioning systems. In this study, in order to increase the performance of the air conditioning system in vehicles, a detailed exergy analysis has been made with the assumption that different refrigerants are used. R-134A, R-E245cb2, R-404A, R-1234ze(Z), R-161, R-1234zd(E), R-513A, R-1234ze(E) and R-1234yf has been chosen as the refrigerant. In the analysis, a comparison has been made by considering the environment, performance and safety values. While the COP values of the cycles increase with increasing evaporator temperatures, the COP values decrease at increasing condenser temperatures. On the other hand, exergy efficiency decreases with increasing evaporator and condenser temperatures. Also it is aimed to evaluate all the elements of a vehicle air conditioning system with exergy analysis.